2006
DOI: 10.1007/s11102-006-0265-2
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary pathology in patients with Carney Complex: growth-hormone producing hyperplasia or tumors and their association with other abnormalities

Abstract: First described in the mid 80's, Carney Complex (CNC) is a rare, dominantly heritable disorder with features overlapping those of McCune-Albright syndrome (MAS) and other multiple endocrine neoplasia (MEN) syndromes like MEN type 1 (MEN 1). Pituitary tumors have been described in a number of patients with CNC; they present with elevated growth hormone (GH) levels and mild hyperprolactinemia. However, most patients with CNC have mild hypersomatomammotropinemia starting in adolescence; this is similar to the sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 37 publications
0
34
1
2
Order By: Relevance
“…Pituitary hyperplasia is, however, characteristic of patients with CNC and acromegaly (Pack et al 2000), although the tumor multicentricity seen in CNC has not been seen to date in the setting of AIP mutations. In contrast to the tumors in this study where the hyperplastic areas were immunoreactive for GH only, pituitary hyperplasia in CNC is characterized by GH and prolactin immunoreactivity (Boikos & Stratakis 2006). McCune-Albright syndrome (MAS) is also associated with acromegaly and disorders of both GH and prolactin secretion in which diffuse somatomammotrope hyperplasia accompanying the adenoma has been described (Kovacs et al 1984, Dumitrescu & Collins 2008.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Pituitary hyperplasia is, however, characteristic of patients with CNC and acromegaly (Pack et al 2000), although the tumor multicentricity seen in CNC has not been seen to date in the setting of AIP mutations. In contrast to the tumors in this study where the hyperplastic areas were immunoreactive for GH only, pituitary hyperplasia in CNC is characterized by GH and prolactin immunoreactivity (Boikos & Stratakis 2006). McCune-Albright syndrome (MAS) is also associated with acromegaly and disorders of both GH and prolactin secretion in which diffuse somatomammotrope hyperplasia accompanying the adenoma has been described (Kovacs et al 1984, Dumitrescu & Collins 2008.…”
Section: Discussioncontrasting
confidence: 76%
“…Owing to this lack of suggestive symptoms or signs in advance of emergency presentation, the standard hormonal workup (including dynamic pituitary function tests) was not available before surgery. For this reason, although the current patients were unlikely to have the very elevated GH levels and concomitant symptoms typical of AIP-mutation-related somatotropinomas , more subtle abnormalities in the somatotrope axis such as those commonly seen in CNC cannot be ruled out (Boikos & Stratakis 2006). The pathological designation is suggested by the presence of scattered GH-positive cells ( Figs 3C and 4C) and immunoreactivity for Pit-1 (Figs 3E and 4E).…”
Section: Discussionmentioning
confidence: 80%
“…Recently, a mutation in the CDKN1B gene (also known as p27/ KIP1) was reported to be associated with a MEN 1-like syndrome in a rat model and few humans [99]. Genetic defects in one of the regulatory subunits of protein kinase A (PKA) (regulatory subunit type 1 alpha, PRKAR1A) causes Carney complex [100]. Vierimaa (2006) reported that inactivating mutations of the gene encoding aryl hydrocarbon receptor-interacting protein (AIP) were found in patients with pituitary tumors (predominantly acromegaly) in both sporadic and familial settings [101].…”
Section: Molecular Genetics Of Pituitary Tumorsmentioning
confidence: 99%
“…This change in clinical phenotype in patients with concurrent Cushings syndrome and acromegaly is not surprising given the known relationship between cortisol and growth hormone metabolism, but as phenomenon deserves further investigation in patients affected with CNC or similar conditions, such as McCune Albright syndrome [34] For patients with CNC who have elevated GH and/or IGF-1, it is important to identify clinically significant acromegaly as defined by generally applied criteria [69]. Most CNC patients will have some abnormality of GH secretion due to the underlying pituitary hyperplasia, but almost all of them will have negative imaging studies [100,108]. It is common practice to treat CNC patients with elevated IGF-1 levels with somatostatin analogues with the goal of normalizing IGF-1 [100,109].…”
Section: Molecular Genetics Of Pituitary Tumorsmentioning
confidence: 99%
See 1 more Smart Citation